Relationship Between Attitude and Knowledge Towards Level of Compliance in Taking Medication - Putri, Ni Luh Eka Sudiawati; Saputra, Yoga Dwi; Adni, Azizatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hypertension, one of the most common chronic non-communicable diseases, is often undetected and has become a leading cause of mortality worldwide. This worry emphasizes how crucial it is to carry out this inquiry. This study sought to ascertain the association between the level of medication adherence and the knowledge and attitude of hypertension patients at Tanjung Karang Public Health Center. This study used a cross-sectional methodology, purposive sampling, and a correlational analytical design. Correlational analysis was done on the 51 respondents that made up the sample. A validated questionnaire was used to gather data, and the Statistical Program for the Social Sciences (SPSS) was used to evaluate the results using the Spearman's Rho test. The majority of respondents were over 45 years old (72.55%), male (52.94%), had completed senior high school (35.29%), and worked as fishermen, farmers, or housewives (56.86%). Most respondents had low levels of knowledge (94.12%) and a positive attitude toward treatment (68.63%). The majority had a moderate level of medication adherence (82.35%), with no respondents categorized as having low adherence (0%). The test results showed no significant relationship between attitude and adherence (r = 0.134; p = 0.347), and no significant relationship between knowledge and adherence (r = -0.009; p = 0.951).